Preparation method and application of p-aminobenzene sulfonic acid blended nanofiltration membrane
The blended nanofiltration membrane was prepared by blending p-aminobenzenesulfonic acid and piperazine and interfacial polymerization method, which solved the problem between traditional polymer films in improving interception and permeability, and achieved a high permeability and high selectivity nanofiltration membrane, which significantly improved the cobalt lithium separation efficiency.
Patent Information
- Application Number
- CN202510280572.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-11
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2045-03-11
AI Technical Summary
It is difficult to improve the permeability flux while increasing the retention rate, and traditional polyamide films have problems such as insufficient hydrophilicity, poor permeability, low retention efficiency, poor thermal stability and easy contamination.
A blended nanofiltration membrane was prepared by blending p-aminobenzenesulfonic acid and piperazine through interfacial polymerization. The polyamide network of sulfonic acid groups of p-aminobenzenesulfonic acid was modified to form an ordered nanochannel structure to enhance the permeability and retention of the membrane.
A nanofiltration membrane with high permeability and high selectivity is achieved, breaking the trade off effect between permeability and retention in traditional films, significantly improving the cobalt lithium separation efficiency, and having better water flux and enrichment rate.
Smart Images

Figure CN119838440A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a preparation method of a nanofiltration membrane for improving cobalt-lithium separation performance and application thereof. Background Art
[0002] Cobalt and lithium, as two core strategic metals, are widely used in lithium-ion batteries for electric vehicles, electronic devices, and energy storage. They often coexist in the cathode materials of waste lithium-ion batteries, and must be effectively separated during recycling. It is predicted that by 2050, the global demand for cobalt will surge several times, and the demand for lithium will also increase significantly. This surge in demand is due to the booming electric vehicle industry, the popularity of electronic devices, and the increasing demand for energy storage. With the rapid consumption of these devices and the lack of responsibility of some users, a large amount of resources are wasted. These aqueous waste streams contain huge potential for the recovery of cobalt and lithium, which provides the possibility of resource reuse. Therefore, the global recovery of these strategic metals and wastewater treatment is not only necessary to implement the concept of circular economy, but also the key to protecting natural resources and minimizing the burden on the environment.
[0003] At present, membrane separation technology does not involve phase change process, so its energy consumption is relatively low. Compared with traditional separation methods, it can significantly reduce energy consumption and reduce carbon emissions. Among them, nanofiltration membrane has good ion selectivity and can achieve the interception or permeation of specific ions by adjusting the pore size and charge properties of the membrane according to actual needs. Therefore, it is widely used in municipal water supply, wastewater treatment, food and beverage processing, pharmaceutical manufacturing and other fields. At the same time, the interfacial polymerization method has become the mainstream method for preparing nanofiltration membranes in the world because of its simple process for preparing polyamide thin films, low cost and ability to prepare films with superior performance. Although the TFC membrane (polyamide nanofiltration membrane) prepared by interfacial polymerization has made certain progress, it still faces the common problems of traditional polyamide membranes, such as insufficient hydrophilicity, poor permeability, low interception efficiency, poor thermal stability and easy pollution. Therefore, how to develop a nanofiltration membrane with both high permeability and high selectivity has become a hot spot and difficulty in the current research field. Summary of the invention
[0004] The present invention aims to solve the technical problem that it is difficult for existing polymer films to improve the interception rate of the membrane and the permeation flux at the same time, and provides a preparation method of a p-aminobenzenesulfonic acid blended nanofiltration membrane and its application.
[0005] The preparation method of the p-aminobenzenesulfonic acid blended nanofiltration membrane of the present invention is carried out according to the following steps:
[0006] 1. mixing p-aminobenzenesulfonic acid and piperazine in water to obtain a mixed aqueous solution;
[0007] The concentration of PIP (piperazine) in the mixed aqueous solution is 10 g / L to 18 g / L, and the concentration of p-aminobenzenesulfonic acid is 0.5 g / L to 5.5 g / L;
[0008] 2. Clean the polyethersulfone membrane with anhydrous ethanol and then dry it; then immerse the dried polyethersulfone membrane in the blend solution prepared in step 1 for 1 to 3 minutes, pour out the liquid, and dry the film naturally in the air to obtain a PIP saturated membrane;
[0009] 3. Immerse the PIP saturated membrane prepared in step 2 in a n-hexane solution of TMC (trimethylenediamine chloride) for 20s to 100s to cause an interfacial polymerization reaction, pour out the liquid, and then place the film in a drying oven for heat treatment for 23min to 27min at a heat treatment temperature of 50°C to 70°C to obtain a p-aminobenzenesulfonic acid blended nanofiltration membrane;
[0010] The concentration of the TMC n-hexane solution is 0.2 g / L to 1.5 g / L.
[0011] The p-aminobenzenesulfonic acid blended nanofiltration membrane prepared by the present invention is used for selectively separating cobalt and lithium ions in cobalt oxide lithium battery acid leaching wastewater. The specific method is: adjusting the pH of the cobalt oxide lithium battery acid leaching wastewater to 1-2, and then filtering through the p-aminobenzenesulfonic acid blended nanofiltration membrane to selectively separate the cobalt and lithium ions.
[0012] The p-aminobenzenesulfonic acid blended nanofiltration membrane prepared by the present invention breaks the trade-off effect between the permeability and the rejection rate of traditional polymer membranes, and at the same time achieves a higher cobalt-lithium separation efficiency.
[0013] The rejection rate, separation factor and water flux are three important parameters for evaluating the nanofiltration membrane, and the rejection rate, separation factor and water flux are used to evaluate the performance of the present invention.
[0014] The interception rate R (%) is defined as: under certain operating conditions, the concentration of a specific substance in the raw material solution (C p ) and the concentration in the permeate (C f ) and the percentage of the concentration in the raw material solution:
[0015]
[0016] Separation factor S Co,Li It is defined as: under certain operating conditions, Li + The ion concentration (C Li,p ) and Co in the permeate 2+ The ion concentration (C Co,p ) ratio, and the Li + The ion concentration (C Li,f) and Co in the raw material solution 2+ The ion concentration (C Co,f ) ratio:
[0017]
[0018] Water flux is defined as the volume of water that passes through a unit membrane area per unit time under certain operating conditions. The unit in this invention is L / (m 2 h).
[0019] Compared with the prior art, the present invention has the following beneficial effects:
[0020] The invention dopes p-aminobenzenesulfonic acid in the process of preparing a traditional TFC composite membrane, utilizes the sulfonic acid group of p-aminobenzenesulfonic acid to modify the TFC membrane, and compares the molecular configuration differences of p-aminobenzenesulfonic acid, o-aminobenzenesulfonic acid and m-aminobenzenesulfonic acid, and finds that p-aminobenzenesulfonic acid exhibits better reaction activity in the interfacial polymerization process due to its smaller steric hindrance effect, and the efficient introduction of the sulfonic acid group (-SO H) promotes the formation of an ordered nanochannel structure in the polyamide network, and the hydrophilic sulfonic acid group enables the flux of the membrane to be improved, thereby adjusting the filtration speed of the permeation rate of pure water; at the same time, because the sulfonic acid group carries negative charge, the electronegativity of the entire membrane is enhanced, and the Co 2+ The repellency is significantly higher than that of Li + , enabling selective separation, ultimately affecting the membrane's permeability to water and separation of metal ions in wastewater.
[0021] The present invention uses a blended liquid of optimized low monomer concentration PIP and p-aminobenzenesulfonic acid and TMC to form a thinner polyamide selective layer on the surface of the polyethersulfone support layer, and obtains a good nanofiltration thickness; the introduction of the sulfonic acid group of p-aminobenzenesulfonic acid greatly improves the water flux and enrichment rate of the membrane. The nanofiltration membrane prepared by the present invention has better permeability and retention than the traditional TFC membrane, and has the hydrophilicity, antibacterial property and thermal stability of the nanofiltration material, and can be widely used in the separation of various salts. At the same time, the membrane is used for the first time to treat the acid leaching wastewater of the positive electrode material of cobalt lithium battery. The maximum retention rates of monovalent lithium ions and divalent cobalt ions are 7.25% and 100% respectively, and the separation factor is 477.2. It has ultra-high selectivity, achieves ultra-high separation effect of cobalt and lithium ions, and can fully retain Co in the wastewater. 2+ At the same time, it can increase the pure water permeation flux of the membrane. The maximum water flux is 12.52L / (m 2 h). BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 is the structural formula of o-aminobenzenesulfonic acid, m-aminobenzenesulfonic acid and p-aminobenzenesulfonic acid;
[0023] Figure 2 This is the data graph of Table 1;
[0024] Figure 3 This is the data graph of Table 2. DETAILED DESCRIPTION
[0025] Specific implementation method 1: This implementation method is a method for preparing a p-aminobenzenesulfonic acid blended nanofiltration membrane, which is specifically carried out according to the following steps:
[0026] 1. mixing p-aminobenzenesulfonic acid and piperazine in water to obtain a mixed aqueous solution;
[0027] The concentration of PIP in the mixed aqueous solution is 10 g / L to 18 g / L, and the concentration of p-aminobenzenesulfonic acid is 0.5 g / L to 5.5 g / L;
[0028] 2. Clean the polyethersulfone membrane with anhydrous ethanol and then dry it; then immerse the dried polyethersulfone membrane in the blend solution prepared in step 1 for 1 to 3 minutes, pour out the liquid, and dry the film naturally in the air to obtain a PIP saturated membrane;
[0029] 3. Immerse the PIP saturated membrane prepared in step 2 in a n-hexane solution of TMC for 20s to 100s to cause an interfacial polymerization reaction, pour out the liquid, and then place the film in a drying oven for heat treatment for 23min to 27min at a heat treatment temperature of 50°C to 70°C, and prepare a nanofiltration membrane blended with p-aminobenzenesulfonic acid;
[0030] The concentration of the TMC n-hexane solution is 0.2 g / L to 1.5 g / L.
[0031] Specific implementation method 2: This implementation method is different from specific implementation method 1 in that: the blending method in step 1 is ultrasound + stirring for 5 minutes to 10 minutes at the same time. The rest is the same as specific implementation method 1.
[0032] Specific implementation method 3: This implementation method is different from specific implementation method 2 in that the frequency of ultrasound in step 1 is 30kHz to 40kHz. The rest is the same as specific implementation method 2.
[0033] Specific embodiment 4: This embodiment is different from specific embodiments 1 to 3 in that: in step 2, the polyethersulfone membrane is cleaned with anhydrous ethanol and then dried. The specific process is: the polyethersulfone membrane is soaked in anhydrous ethanol for 2h to 3h to remove surface impurities, improve the hydrophilicity of the polyethersulfone membrane surface, and then dried at 60°C for 10min. The rest is the same as specific embodiments 1 to 3.
[0034] Specific embodiment 5: This embodiment is an application of the p-aminobenzenesulfonic acid blended nanofiltration membrane in specific embodiment 1, specifically for selectively separating cobalt and lithium ions in acid leaching wastewater of lithium cobalt oxide batteries.
[0035] Specific embodiment 6: This embodiment is different from specific embodiment 5 in that: the specific method for selectively intercepting the cobalt element in the acid leaching wastewater of lithium cobalt oxide battery is: adjusting the pH of the acid leaching wastewater of lithium cobalt oxide battery to 1-2, and then filtering through the p-aminobenzenesulfonic acid blended nanofiltration membrane to selectively separate the cobalt and lithium ions. The rest is the same as specific embodiment 5.
[0036] Specific embodiment 7: This embodiment is different from the specific embodiment 6 in that the metal ions in the acid leaching wastewater of the lithium cobalt oxide battery positive electrode material are Li + and Co 2+ , and Li + The concentration is 50mg / L~100mg / L, Co 2+ The concentration is 100 mg / L to 300 mg / L. Other aspects are the same as those of the sixth embodiment.
[0037] The present invention is verified by the following tests:
[0038] Experiment 1: This experiment is a method for preparing a p-aminobenzenesulfonic acid blended nanofiltration membrane, which is specifically carried out in the following steps:
[0039] 1. Blending p-aminobenzenesulfonic acid and piperazine in water, the blending method is ultrasonic + stirring for 10 minutes, the frequency of ultrasound is 35kHz, to obtain a blended aqueous solution;
[0040] The concentration of PIP in the blended aqueous solution is 17.5 g / L, and the concentration of p-aminobenzenesulfonic acid is 0.875 g / L;
[0041] 2. Soak the polyethersulfone membrane in anhydrous ethanol for 2 hours to intercept surface impurities and improve the hydrophilicity of the polyethersulfone membrane surface, and then dry it at 60° C. for 10 minutes; then immerse the dried polyethersulfone membrane in the blended solution prepared in step 1 for 2 minutes, pour out the liquid, and naturally dry the film in the air to obtain a PIP saturated membrane;
[0042] 3. Immerse the PIP saturated membrane prepared in step 2 in a n-hexane solution of TMC for 60 seconds to cause an interfacial polymerization reaction, pour out the liquid, and then place the film in a drying oven for heat treatment for 25 minutes at a temperature of 60°C to obtain a p-aminobenzenesulfonic acid blended nanofiltration membrane, recorded as M-1;
[0043] The concentration of the TMC n-hexane solution is 1.75 g / L.
[0044] Experiment 2: This experiment differs from Experiment 1 in that the concentration of p-aminobenzenesulfonic acid in step 1 is 1.75 g / L. Others are the same as Experiment 1. The final nanofiltration membrane is recorded as M-2.
[0045] Experiment 3: This experiment differs from Experiment 1 in that the concentration of p-aminobenzenesulfonic acid in step 1 is 3.5 g / L. Others are the same as Experiment 1. The final nanofiltration membrane is recorded as M-3.
[0046] Experiment 4: This experiment differs from Experiment 1 in that the concentration of p-aminobenzenesulfonic acid in step 1 is 4.375 g / L. Others are the same as Experiment 1. The nanofiltration membrane finally obtained is recorded as M-4.
[0047] Experiment 5: This experiment differs from Experiment 1 in that the concentration of p-aminobenzenesulfonic acid in step 1 is 5.25 g / L. Others are the same as Experiment 1. The nanofiltration membrane finally obtained is recorded as M-5.
[0048] Comparative Example 1: This experiment differs from Experiment 1 in that p-aminobenzenesulfonic acid is not added in Step 1. The rest is the same as Experiment 1. The nanofiltration membrane finally obtained is recorded as M-0.
[0049] Comparative Example 2: This experiment differs from Experiment 1 in that anthranilic acid with a concentration of 1.75 g / L is added in Step 1. The rest is the same as Experiment 1. The nanofiltration membrane finally obtained is recorded as M-6.
[0050] Comparative Example 3: This experiment differs from Experiment 1 in that m-aminobenzenesulfonic acid at a concentration of 2.625 g / L is added in Step 1. The rest is the same as Experiment 1. The final nanofiltration membrane is recorded as M-7.
[0051] Application Example 1:
[0052] The nanofiltration membranes prepared in the above-mentioned Experiment 1 to Comparative Example 3 were respectively placed in ultrafiltration cups and fixed. 30 mL of deionized water was added to the ultrafiltration cups, which were sealed and connected to an air compressor and the ultrafiltration cups. The membranes were pre-pressed for the first time at a pressure of 2 bar. After the membranes were pre-pressed, a stopwatch and a measuring cylinder were used to measure the volume of liquid passing through the membrane per unit time. The water flux was calculated according to the following formula:
[0053]
[0054] Where: J is the flux L / (m 2 ·h), T is the test time (h), V is the volume of aqueous solution that permeates the membrane within time T (L), and A is the effective membrane area (m 2 ).
[0055] According to the above formula, the pure water flux of each nanofiltration membrane under a pressure of 2 bar can be calculated. The specific results are shown in Table 1.
[0056] Application Example 2: Prepare Li with an initial concentration of 0.55 g / L + Aqueous solution and 4g / L Co 2+ 5 mL of each aqueous solution was mixed in a 100 mL volumetric flask, fixed to volume with deionized water, and adjusted to pH 1.6 with hydrochloric acid; then 20 mL of the mixed solution was added to the ultrafiltration cup, sealed and connected to the air compressor and the ultrafiltration cup, and the mixed solution was filtered through the nanofiltration membrane prepared in Experiment 1 to Comparative Example 1 at a pressure of 2 bar. The feed liquid and the permeate were filtered with a 0.22 μm filter head, and 1 portion of the filtered feed liquid and the permeate were taken, 1% concentrated nitric acid was added, and then diluted 100 times with ultrapure water, and the Co in it was detected by a flame atomic absorption spectrophotometer. 2+ and Li + The retention rate and separation factor are two important parameters for evaluating the separation performance of nanofiltration membranes.
[0057]
[0058] Where: R is the interception rate (%), C p is the concentration of ions in the raw material solution (mg / L), C f is the concentration of ions in the permeate (mg / L).
[0059] According to the above formula, the Li in the feed liquid can be calculated + The solution concentration is 27.5 mg / L, Co 2+ When the solution concentration is 200 mg / L, the p-aminobenzenesulfonic acid blend nanofiltration membrane is effective for Co 2+ and Li + The specific results are shown in Table 1.
[0060] Table 1 Nanofiltration membrane performance
[0061]
[0062] As can be seen from Table 1, the addition of p-aminobenzenesulfonic acid promotes the pure water flux and interception performance of the nanofiltration membrane. The pure water flux of the nanofiltration membrane with the highest pure water flux can reach 15.78L / (m 2 h), but the separation performance is poor. When the pure water flux reaches 10.74L / (m 2 h) (M-3), the separation effect is optimal, and Co in the wastewater can be fully retained. 2+ , while Li +The interception was kept below 5%. By comparing the addition effects of o-aminobenzenesulfonic acid and m-aminobenzenesulfonic acid, it was found that p-aminobenzenesulfonic acid can be more effectively embedded in the interfacial polymerization reaction system due to its small molecular steric hindrance, thereby significantly improving the water flux performance of the composite membrane. At the same time, p-aminobenzenesulfonic acid showed the best embedding ability in the interfacial polymerization process, thereby significantly improving the separation performance of the blended membrane. Figure 2 This is a graph of the data in Table 1.
[0063]
[0064] In the above formula, S Co,Li For the membrane to Co 2+ and Li + The separation factor, C Li,f Li in the raw material solution + The ion concentration, C Co,f Co in the raw material solution 2+ The ion concentration, C Li,p is the Li in the permeate + The ion concentration, C Co,p is Co in the permeate 2+ According to the above formula, the ion concentration of Li in the raw material solution can be calculated. + The concentration is 27.5 mg / L, Co 2+ When the concentration of p-aminobenzenesulfonic acid is 200 mg / L, the p-aminobenzenesulfonic acid blend nanofiltration membrane has good performance on the Co 2+ and Li + The specific results are shown in Table 2.
[0065] Table 2 Nanofiltration membrane for Co 2+ and Li + Separation factor
[0066]
[0067] It can be seen from Table 2 that the addition of p-aminobenzenesulfonic acid promotes the separation performance of the nanofiltration membrane. The nanofiltration membrane M-3 with the highest separation performance has a good effect on Li + and Co 2+ The maximum separation factor is 477.2, with ultra-high selectivity, achieving high separation of cobalt and lithium elements, laying a good foundation for subsequent recovery. Figure 3 This is the data graph of Table 2.
Claims
1. A method for preparing a p-aminobenzenesulfonic acid blended nanofiltration membrane, characterized in that The preparation method of the p-aminobenzenesulfonic acid blended nanofiltration membrane is carried out according to the following steps:
1. mixing p-aminobenzenesulfonic acid and piperazine in water to obtain a mixed aqueous solution; The concentration of piperazine in the mixed aqueous solution is 10 g / L to 18 g / L, and the concentration of p-aminobenzenesulfonic acid is 0.5 g / L to 5.5 g / L; 2. Clean the polyethersulfone membrane with anhydrous ethanol and then dry it; then immerse the dried polyethersulfone membrane in the blend solution prepared in step 1 for 1 to 3 minutes, pour out the liquid, and dry the film naturally in the air to obtain a PIP saturated membrane; 3. Immerse the PIP saturated membrane prepared in step 2 in a n-hexane solution of TMC for 20s to 100s to cause an interfacial polymerization reaction, pour out the liquid, and then place the film in a drying oven for heat treatment for 23min to 27min at a heat treatment temperature of 50°C to 70°C to obtain a p-aminobenzenesulfonic acid blended nanofiltration membrane; The concentration of the TMC n-hexane solution is 0.2 g / L to 1.5 g / L.
2. The method for preparing a p-aminobenzenesulfonic acid blended nanofiltration membrane according to claim 1, characterized in that The blending method in step 1 is ultrasonication + stirring for 5 minutes to 10 minutes.
3. The method for preparing a p-aminobenzenesulfonic acid blended nanofiltration membrane according to claim 2, characterized in that The frequency of ultrasound in step 1 is 30kHz to 40kHz.
4. The method for preparing a p-aminobenzenesulfonic acid blended nanofiltration membrane according to claim 1, characterized in that In step 2, the polyethersulfone membrane is cleaned with anhydrous ethanol and then dried. The specific process is: the polyethersulfone membrane is immersed in anhydrous ethanol for 2h to 3h to remove surface impurities and improve the hydrophilicity of the polyethersulfone membrane surface, and then dried at 60°C for 10min.
5. An application of a p-aminobenzenesulfonic acid blended nanofiltration membrane as claimed in claim 1, characterized in that The p-aminobenzenesulfonic acid blended nanofiltration membrane is used to selectively separate cobalt and lithium ions from the acid leaching wastewater of lithium cobalt oxide batteries.
6. An application of a p-aminobenzenesulfonic acid blended nanofiltration membrane according to claim 5, characterized in that The specific method for selectively separating the cobalt element in the acid leaching wastewater of lithium cobalt oxide battery is as follows: adjusting the pH of the acid leaching wastewater of lithium cobalt oxide battery to 1-2, and then filtering through the p-aminobenzenesulfonic acid blended nanofiltration membrane to selectively separate the cobalt and lithium ions.
7. An application of a p-aminobenzenesulfonic acid blended nanofiltration membrane according to claim 6, characterized in that The metal ions in the acid leaching wastewater of the lithium cobalt oxide battery positive electrode material are Li + and Co 2+ , and Li + The concentration is 50mg / L~100mg / L, Co 2+ The concentration is 100mg / L~300mg / L.
Citation Information
Patent Citations
Preparation method of nano material modified poly piperazine amide nanofiltration membrane
CN103877872A
Composite ultrafiltration membrane and preparation method thereof
CN116196759A
Preparation method and application of thin film nano composite film with polydopamine coated aminated multi-walled carbon nanotube as middle layer
CN116392984A
Preparation method of high-performance PVDF nanofiltration membrane
CN119034486A
Composite semipermeable membrane and method for manufacturing same
WO2015046582A1